Pengaruh Rekomendasi Content Creator Terhadap Keputusan Pembelian Melalui Interaksi Parasosial Dan Kepercayaan Kreator - Muhammad Satrya Daffa Abhinaya; Farida Indriani (Diponegoro Journal of Management, 2026)
This study aims to examine the effect of content creator recommendations on purchase decisions by considering the mediating roles of parasocial interaction and creator trust. The results indicate that content creator recommendations have a significant positive effect on parasocial interaction, which in turn significantly influences creator trust, and ultimately affects purchase decisions. However, both content creator recommendations and parasocial interaction do not have a direct significant effect on purchase decisions. These findings suggest that the influence of recommendations on purchase decisions occurs indirectly through mediation mechanisms, both partially through parasocial interaction and sequentially through parasocial interaction and creator trust. Therefore, creator trust emerges as a key determinant in driving consumer purchase decisions in the context of social media-based digital marketing.